2019
DOI: 10.1101/727685
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genotype-by-environment interactions for seminal fluid expression and sperm competitive ability

Abstract: Sperm competition commonly occurs whenever females mate multiply, leading to variation in male paternity success. This can be due to variation in the various traits that might affect sperm competitive ability, which itself depends on both genetic and environmental factors, as well as on genotype‐by‐environment interactions (GEI). Seminal fluid is a major component of the male ejaculate that is often expected to mediate sperm competition, where different genotypes can differ in their seminal fluid expression as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 117 publications
(163 reference statements)
0
3
0
Order By: Relevance
“…Although perhaps not dramatic in the sense that sucking never approached 100%, we nevertheless should consider that this effect, coupled with the variation we have described, certainly implies that the effects could be significant in nature. Importantly, a separate study investigating natural variation in the expression of suckless-1 and suckless-2 generated through genotype 3 environment interactions has now revealed a strong positive correlation between suckless-1 expression and defensive sperm competitive ability, P 1 [52], supporting the notion that this protein has functionally significant effects under sperm competition.…”
Section: Rnai Confirms Two Seminal Fluid Transcripts Affect Partner Suck Propensitymentioning
confidence: 87%
“…Although perhaps not dramatic in the sense that sucking never approached 100%, we nevertheless should consider that this effect, coupled with the variation we have described, certainly implies that the effects could be significant in nature. Importantly, a separate study investigating natural variation in the expression of suckless-1 and suckless-2 generated through genotype 3 environment interactions has now revealed a strong positive correlation between suckless-1 expression and defensive sperm competitive ability, P 1 [52], supporting the notion that this protein has functionally significant effects under sperm competition.…”
Section: Rnai Confirms Two Seminal Fluid Transcripts Affect Partner Suck Propensitymentioning
confidence: 87%
“…Many subsequent studies extensively documented within‐population variation of SFPs using inbred families from a single population, particularly focusing on the influence on sperm competition (e.g. sequence: Clark, Aguadé, Prout, Harshman, & Langley, 1995; Fiumera, Dumont, & Clark, 2005; Fiumera, Dumont, & Clark, 2007; Zhang, Clark, & Fiumera, 2013, gene expression: Patlar, Weber, & Ramm, 2019; Patlar & Ramm, 2020, protein abundance: Brandon, Heusnes, Caudle, & Fayrer‐Hosken, 1999). More direct attempts to compare SFP divergence between populations have recently begun, providing empirical support for diversified SFPs, likely associating with differential effects (protein abundance: Baer, Zareie, Paynter, Poland, & Millar, 2012; Goenaga, Yamane, Rönn, & Arnqvist, 2015; Mangels et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…normal atmosphere vs. high CO 2 concentration) than P2 in Drosophila melanogaster [48]. Moreover, variation of SFP gene expression generated through genotype-by-environment interactions in competitive and non-competitive settings found a positive relationship between gene expression and P1 but not P2 in flatworms [49]. The use of experimental evolution to enforce monogamy in Drosophila has also shown that monogamous males become weaker sperm competitors and have lower expression of SFPs, but do not differ from polygamous males in their ability to diminish female remating [50].…”
Section: Discussionmentioning
confidence: 87%